KONSEP “HUKUM SEKSUAL” SEBAGAI INSTRUMEN PERLINDUNGAN HUKUM YANG BERKEADILAN BAGI PEMBUAT VIDEO MESRA (SEX TAPE MAKER) - Pirena Putri, Revita; Laura Bachsin, Jennifer; Mangesti, Yovita Arie (Faculty of Law, Universitas 17 Agustus 1945 Surabaya, 2021)
AbstractThe evolution of the era from time to time, forming technology even more sophisticated. Capturing moments with your lover such as recording intimate videos is something that is often done by many people, especially adolescent. But in recording the video, there are several things that need to be considered. For example, there must be an agreement or consent between the two parties so there’s no misleading which could be categorized as a criminal act of pornography. If that happens, then there is a need for a “legal umbrella” that protects the video makers. Hitherto, the “legal umbrella” about the form of legal protection for these intimate video makers has not been clearly written. In this study, the authors used a juridical normative method, based on acts as the basis for the research. The acts that are used as a reference are Acts 44 of 2008 concerning Pornography, Government Regulation 71 of 2019 concerning Implementation of Electronic Systems and Transactions, and Act 19 of 2016 concerning Amendments to Acts 11 of 2008. regarding Electronic Information and Transactions. Furthermore, the author also used a descriptive method which undertake research using data that was taken from the society through an online seminar to find out the society perspective about recording intimate videos which is the topic of the author's research.Keywords: consent; intimate videos; legal protectionAbstrakPerkembangan zaman membuat teknologi menjadi semakin canggih dan digunakan di segala bidang. Teknologi membawa perubahan gaya hidup. Kebiasaan mengabadikan momen dengan pasangan seperti membuat video mesra merupakan gaya hidup yang kerap kali dilakukan oleh banyak orang, terutama dari kalangan muda. Tetapi dalam pembuatan video tersebut, ada beberapa hal yang perlu diperhatikan, yaitu harus ada persetujuan atau consent antara kedua belah pihak agar hal ini tidak berujung pada tindak pidana pornografi. Pembuatan video yang bertujuan untuk dokumentasi pribadi berkemungkinan untuk menjadi objek Dalam penelitian ini, peneliti menggunakan metode pendekatan perundang-undang, dengan berdasarkan pada undang-undang sebagai dasar penelitian. Undang-Undang yang dijadikan sebagai acuan penelitian adalah UU No. 44-2008. Selain itu, peneliti juga menggunakan metode deskriptif kualitatif, yang mana dalam hal ini peneliti melakukan penelitian dari random sampling data kuisioner yang diambil di masyarakat melalui sebuah seminar online guna mengetahui pemikiran dan pandangan masyarakat tentang pembuatan video mesra yang menjadi topik penelitian peneliti.